2014
DOI: 10.1515/multi-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

‘You need help as usual, do you?’: Joking and swearing for collegiality in a Swedish workplace

Abstract: This paper draws on the KINSA project (The Communicative Situation of Immigrants at Swedish Workplaces), which aimed to identify communicative factors that have a positive impact on the integration of second language speakers in the workplace and in their immediate work team. The focus here is on humour and swearing as strategies for doing collegiality and for building and maintaining good relations between co-workers. The article presents data from five second language speakers, permanently employed industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 0 publications
0
16
0
10
Order By: Relevance
“…These claims were also supported by Schaeffer and Bukenya (2010), who found that language was a determining factor when it comes to social integration of immigrants at the workplace. Nelson's (2014) research was also somewhat consistent with the aforementioned studies because her study suggested that the second language should be used strategically to "foster good relations at work" and to "facilitate and consolidate integration in the workplace" (p. 173). This implies that Nelson (2014) also linked local language competence to workplace integration of immigrants.…”
Section: Accent Discriminationmentioning
(Expert classified)
See 3 more Smart Citations
“…These claims were also supported by Schaeffer and Bukenya (2010), who found that language was a determining factor when it comes to social integration of immigrants at the workplace. Nelson's (2014) research was also somewhat consistent with the aforementioned studies because her study suggested that the second language should be used strategically to "foster good relations at work" and to "facilitate and consolidate integration in the workplace" (p. 173). This implies that Nelson (2014) also linked local language competence to workplace integration of immigrants.…”
Section: Accent Discriminationmentioning
(Expert classified)
“…Page 18 The data have shown that language competence can be linked to social exclusion. For the blue-collar workers with no English skills as well as other Danes with limited English skills, their lack of language competence means that they are excluded from obtaining basic information at work, and they believe that their lack of language competence prevents them from looking for a better job Nelson (2014) Most studies were qualitative (n=8); two studies used quantitative methods. Of the qualitative studies, there was a case study, a grounded theory study, ethnographic studies (n=3), and thematic analysis studies (n=3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a handful of scholarly works (e.g., ) that have articulated the linguistic features of workplace instant messaging, there has been generally little research on swearing in workplace instant messaging, especially in Asian contexts. Studies on swearing by second language speakers of English have been equally scant (Nelson, 2014). Drawing on sets of English instant messages 1 produced by Hong Kong Chinese workers in two Hong Kong trading firms, this chapter investigates the impact of swearing in instant messaging in the backoffice as well as the involved acting out of identity and power.…”
Section: Introductionmentioning
confidence: 99%